2015
DOI: 10.1093/mnras/stu2761
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical origin of early-type dwarfs in galaxy clusters: a theoretical investigation

Abstract: Observations of early-type dwarf galaxies in clusters often show that cluster dwarf members have significantly higher velocities and less symmetric distributions than cluster giant ellipticals, suggesting that these dwarfs are recently accreted galaxies, possibly from an infalling group. We use a series of N -body simulations, exploring a parameter space of groups falling into clusters, to study the observed velocity distributions of the infall components along various lines of sight. We show that, as viewed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…Based on both measures, Skewness and Kurtosis, we conclude that faint galaxies in NG groups are mainly infalling for the first time in the cluster. Obviously, this result should be seen in average for the family of NGs but it is noticeable that 6 out 9 NG systems have Kurtosis < -0.5, strongly supporting the view that faint galaxies in these systems are in the very early stage of infalling, before the first pericentric passage (see Figure 8a of Vijayaraghavan et al 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Based on both measures, Skewness and Kurtosis, we conclude that faint galaxies in NG groups are mainly infalling for the first time in the cluster. Obviously, this result should be seen in average for the family of NGs but it is noticeable that 6 out 9 NG systems have Kurtosis < -0.5, strongly supporting the view that faint galaxies in these systems are in the very early stage of infalling, before the first pericentric passage (see Figure 8a of Vijayaraghavan et al 2015).…”
Section: Discussionsupporting
confidence: 56%
“…N-body simulations of infalling galaxy groups support their particular phase-space distribution as the result of a galaxy group accretion onto Virgo. According to simulations, this accretion event has taken place 2 to 3 Gyr ago, along the observer's line-of-sight (Vijayaraghavan et al 2015). Such a picture receives further support by studies of Pasquali et al (2019) and Smith et al (2019), who showed that cluster galaxies occupy different zones in the phase-space diagram with respect to their average infall time to cluster.…”
Section: Rementioning
confidence: 78%
“…for signatures of a group infall (see, e.g. Vijayaraghavan et al 2015). On top of the above -and with large enough samples -one should always try to look at any global trends in more than one dimension, plotting them as maps, rather than 1D profiles, thus taking advantage of all the available bits of information on the galaxies.…”
Section: Determining the Dependence Of Galaxy Properties On The Envirmentioning
confidence: 99%